Massive Open Online Courses and Their Opportunities - Usmanova Gulnoza (Zien Journals, 2023)
This article describes public open online courses and their possibilities. Also included is an analysis of public open online courses offered by prestigious universities around the world. The role of public open online courses in the educational process is revealed.
Keywords: public; open; online; course